The Effectiveness of Host Modulation Therapy in Advanced Periodontitis - Mashael Alhumidi Hamed Alharbi,; Tagreed Fahd AlDosry,; Khalid Abdulaziz Alrafie,; Alanoud bassam albalawi,; Sara Nasser Altamimi,; Abdullah Obaid Alamri,; Wessam abdullah Alforaih,; Mohammed Abdullah Alqahtani,; Meshal Fawaz Alshammari,; Ibtihaj Abdulaziz Almutairi,; Sarah Hamed Almutairi,; Abdullah Ebrahim Alkhamis,; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Periodontitis is a chronic inflammatory disease characterized by the destruction of the tooth-supporting tissues, driven by a dysregulated host inflammatory response to the microbial biofilm. Traditional treatment approaches have primarily focused on mechanical debridement and bacterial control, but may not effectively address the underlying host-mediated inflammatory response. Host modulation therapy (HMT) has emerged as a promising approach to modulate the dysregulated host response and promote tissue regeneration. This paper provides an in-depth analysis of the effectiveness of HMT in the treatment of advanced periodontitis, with a focus on chemically modified tetracyclines and curcumin analogues as host modulation agents. The non-antimicrobial properties of these agents, including inhibition of matrix metalloproteinases, suppression of pro-inflammatory cytokines, and promotion of inflammation resolution, are discussed. Clinical and preclinical studies demonstrate the efficacy of HMTs in reducing tissue damage, promoting tissue regeneration, and improving clinical outcomes. Additionally, the potential of pro-resolving therapies, such as specialized pro-resolving mediators and stem cell-based approaches, is explored. While significant progress has been made, further research is needed to optimize HMT and explore its integration with traditional antimicrobial therapies, as well as personalized medicine approaches.